REDUCING STUDENTS’ MISSCONCEPTION IN GEOMETRICAL OPTICS WITH (PROCESS ORIENTED GUIDED INQUIRY LEARNING) - Sri Lestari Handayani; Kusmajid Kusmajid; Mimin Ninawati (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
MEREDUKSI MISKONSEPSI MAHASISWA MATERI OPTIK GEOMETRI MAHASISWA MELALUI PENERAPAN POGIL (PROCESS ORIENTED GUIDED INQUIRY LEARNING)AbstractMisconception becomes one of the causes of understanding students' concepts to be incompatible with scientific concepts. The purpose of this research is to know the application of POGIL model (Process Oriented Guided Inquiry Learning) in reducing misconception of PGSD UHAMKA student in optical geometry subject. The design of this research is experimental research in the form of One Group Pretest-Posttest Design. The population of this research is 3rd year PGSD UHAMKA students who follow the course of physics basic concept. The sample of this research is taken by using purposive sampling as many as 34 students. Data were collected using a written test. The written test used is a multiple-choice, three-tiered diagnostic test. The data of this research were analyzed by analysis of test scans, interpretation analysis of diagnostic tests, misconception rate analysis, and analysis of misconception reduction. Misconception level analysis uses percentages that fall into low, medium, and high categories. The analysis of misconceptions decreased by using the comparison test of student misconceptions scores on pretest and posttest. The highest misconception experienced by students is 49% medium criterion and occurs in indicators understand the process of refraction of light and associated magnitudes. The lowest misconception of 21% with low criterion occurs in the indicators to understand the process of shadow formation in a concave mirror. The mean decrease in misconception of PGSD students after POGIL learning was 8.954%. These results indicate that POGIL can reduce student misconceptions although it is in small category. AbstrakMiskonsepsi menjadi salah satu penyebab pemahaman konsep mahasiswa menjadi tidak sesuai dengan konsep ilmiah. Tujuan penelitian ini adalah untuk mengetahui penerapan model POGIL (Process Oriented Guided Inquiry Learning) dalam mereduksi miskonsepsi mahasiswa PGSD UHAMKA materi optik geometri. Desain penelitian ini adalah penelitian eksperimen berupa One Group Pretest-Posttest Design. Populasi penelitian ini adalah mahasiswa PGSD UHAMKA Semester 5 yang mengikuti mata kuliah Konsep Dasar Fisika. Sampel penelitian ini diambil dengan meggunakan purposive sampling sebanyak 34 mahasiswa. Data dikumpulkan dengan menggunakan tes tertulis. Tes tertulis yang digunakan berupa tes diagnostik pilihan ganda tiga tingkat. Data yang diperoleh kemudian dianalisis dengan analisis penskoran tes, analisis interpretasi tes diagnostik, analisis tingkat miskonsepsi, dan analisis penurunan miskonsepsi. Analisis tingkat miskonsepsi menggunakan prosentase yang termasuk dalam kategori rendah, sedang, dan tinggi. Analisis penurunan miskonsepsi menggunakan uji gain perbandingan skor miskonsepsi mahasiswa pada pretest dan posttestnya. Miskonsepsi tertinggi yang dialami oleh siswa sebesar 49 % berkriteria sedang dan terjadi pada indikator memahami proses pembiasan cahaya dan besaran-besaran yang terkait. Miskonsepsi terendah sebesar 21% berkriteria rendah terjadi pada indikator memahami proses pembentukan bayangan pada cermin cekung. Rata-rata penurunan miskonsepsi mahasiswa PGSD setelah pembelajaran POGIL sebesar 8,954%. Hasil tersebut menunjukkan bahwa POGIL dapat mereduksi miskonsepsi mahasiswa meskipun tergolong kecil.